Are consumers willing to pay more for reformulated processed meat products in the context of the implementation of nutritional warnings? Case study with frankfurters in Chile. (June 2019) - Schnettler, Berta; Ares, Gastón; Sepúlveda, Néstor; Bravo, Silvana; Villalobos, Blanca; Hueche, Clementina; Lobos, Germán
Abstract: The aim of the present work was to assess consumers' willingness to pay for reformulated frankfurters in the context of the implementation of nutritional warnings. Images of frankfurter packages were designed using a fractional factorial design with 5 2-level variables: brand type, sodium reduction, saturated fat reduction, fibre claim and cholesterol claim. An online study with 548 consumers was implemented with Chilean participants, who were asked to indicate how much they would be willing to pay for each of the packages. Data were analysed using analysis of variance and hierarchical cluster analysis. Willingness to pay was significantly affected by brand type and sodium and fat reduction, whereas fibre and cholesterol claim did not have a significant effect. These results suggest that in the context of the implementation of nutritional warnings reformulation of processed meat products should focus on the reduction of key nutrients, although consumers may not be willing to pay a higher price for reformulated products.